Pengaruh ekstrak daun kersen terhadap daya tetas dan mortalitas telur itik hibrida - Fatikhatul Huda Alkhakim; Muhammad Ngalaul Huda; Galuh Dianita Fitri; Dewi Ambarwati; Heli Tistiana (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2016)
Duck was one of animal protein resources which still has a low hatchability rate. There were Staphylococcus aureus and Salmonella sp.bacteria on hatch egg that can influence mortality of embryos. The objective of the research was to investigate the potential of Muntingia calabura leaf extract as natural antibacteria on the hatchability and embryos mortality of duck’s egg. The research method was field experiment by completely randomized design with five treatments and four replications: P0 (without treatment), A0 (chemical antibacteria), P1(10% of Muntingia calabura leaf extract), P2 (20% of Muntingia calabura leaf extract) and P3 (30% of Muntingia calabura leaf extract). These research used four hundred eggs and semi automatical machine for 28 days. Data were analyzed using one–way Anova. The results showed that Muntingia calabura leaf extract has a very significant effect (P<0,01) on hatchability and embryos mortality. The best treatment was found on 20% of Muntingiacalabura leaf extract which increased 12,01% ofhatchability and decreased 43,42% of mortality rate. Keywords: Muntingia calabura, antibacteria, hatchability, embryos mortality